Determining the Time Window for Dynamic Nanowire Cell Penetration Processes - Xie, Xi; Aalipour, Amin; Gupta, Sneha V; Melosh, Nicholas A (ACS nano, 2015)
Nanowire (NW) arrays offer opportunities for parallel, nondestructive intracellular access for biomolecule delivery, intracellular recording, and sensing. Spontaneous cell membrane penetration by vertical nanowires is essential for these applications, yet the time- and geometry-dependent penetration process is still poorly understood. In this work, the dynamic NW–cell interface during cell spreading was examined through experimental cell penetration measurements combined with two mechanical models based on substrate adhesion force or cell traction forces. Penetration was determined by comparing the induced tension at a series of given membrane configurations to the critical membrane failure tension. The adhesion model predicts that penetration occurs within a finite window shortly after initial cell contact and adhesion, while the traction model predicts increasing penetration over a longer period. NW penetration rates determined from a cobalt ion delivery assay are compared to the predicted results from the two models. In addition, the effects of NW geometry and cell properties are systematically evaluated to identify the key factors for penetration.